Heat-Induced Limb Length Asymmetry Has Functional Impact on Weight Bearing in Mouse Hindlimbs - Racine, Holly L.; Meadows, Chad A.; Ion, Gabriela; Serrat, Maria A. (Frontiers in Endocrinology, 2018)
Limb length inequality results from many types of musculoskeletal disorders. Asymmetric weight bearing from a limb length discrepancy of less than 2% can have debilitating consequences such as back problems and early onset osteoarthritis. Existing treatments include invasive surgeries and/or drug regimens that are often only partially effective. As a noninvasive alternative, we previously developed a once daily limb-heating model using targeted heat on one side of the body for two weeks to unilaterally increase bone length by up to 1.5% in growing mice. In this study, we applied heat for one week to determine whether these small differences in limb length are functionally significant, assessed by changes in hindlimb weight bearing. We tested the hypothesis that heat induced limb length asymmetry has a functional impact on weight bearing in mouse hindlimbs. Female 3-week old C57BL/6 mice (N=12 total) were treated with targeted intermittent heat for 7 days (40C for 40 min/day). High-resolution x-ray (N=6) and hindlimb weight bearing data (N=8) were acquired at the start and end of the experiments. There were no significant left-right differences in starting tibial length or hindlimb weight bearing. After one week heat exposure, tibiae (t = 7.7, p < 0.001) and femora (t = 11.5, p < 0.001) were ~1% and 1.4% longer, respectively, on the heat-treated sides (40C) compared to the non-treated contralateral sides (30C). Tibial elongation rate was over 6% greater (t = 5.19, p < 0.001). Hindlimb weight bearing was nearly 20% greater (t = 11.9, p < 0.001) and significantly correlated with the increase in tibial elongation rate on the heat-treated side (R2 = 0.82, p < 0.01). These results support the hypothesis that even a small limb length discrepancy can cause imbalanced weight distribution in healthy mice. The increase in bone elongation rate generated by localized heat could be a way to equalize limb length and weight bearing asymmetry caused by disease or trauma, leading to new approaches with better outcomes by using heat to lengthen limbs and reduce costly side effects of more invasive interventions.